Religious Expression of Millenial Muslims within Collective Narcissism Discourse in Digital Era - M. Naufal Waliyuddin (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This article focuses on examining how the religious expression of Indonesian millennial Muslims in the landscape of collective narcissism discourse in the present digital era. This study investigates the social media activities of NU and Muhammadiyah youth organizations, Pemuda Hijrah, Indonesia Tanpa Pacaran, and some of the Radical Groups like ISIS. This study employs discourse analysis with social psychology approach. The result of this research shows that the religious expression of millennial Muslims in Indonesia can be categorized into six types, namely: actual-modernist Islam, cultural-pluralist Islam, liberalist Islam, apathetic Islam, scriptural-fundamentalist Islam, and radical Islam. Whereas in the discourse of collective religious narcissism, based on several cases study show that mainstream Islamic organizations such as NU and Muhammadiyah, the activities can be categorized as positive collective religious narcissism. Meanwhile, Pemuda Hijrah and Indonesia Tanpa Pacaran are categorized as negative collective religious narcissism. This consideration resulted from their claim as of better than the other group. On the other hand, radical group activities such as ISIS is categorized as destructive collective religious narcissism because they claim rigidly and unequivocally accused others sinful, heretic, and astray and deserve to be banished. In other words, this is the phenomenon of religious expression, which ironically, belongs to acute destructive narcissism.